Two new riparian Pselaphinae from Hubei, Central China (Coleoptera: taphylinidae) - Yin, Zi-Wei; Zeng, Ting-Kai (Zootaxa, 2023)
The Pselaphinae fauna of Hubei Province in central China is extremely poorly documented. Here we describe two new species recently collected at a riverbank near Chongyang’s county seat. Batrisiella riparia sp. nov. is characterized by the greatly swollen metafemora of the male, and Nipponobythus varicornis sp. nov. has a darkish-colored body, and uniquely modified male antennal clubs and metaventrite. Illustrations of the habitus and taxonomically informative characters of both species are provided for a reliable identification.